Dietary Omega-3 Fatty Acids, COX-2 Genetic Variation, and Aggressive Prostate Cancer Risk - Fradet, Vincent (2009)
PURPOSE: Dietary intake of long-chain omega-3 polyunsaturated fatty acids (LC n-3) may reduce inflammation and in turn decrease risk of prostate cancer development and progression. This potential effect may be modified by genetic variation in COX-2, a key enzyme in fatty acid metabolism and inflammation. EXPERIMENTAL DESIGN: We used a case-control study of 466 men diagnosed with aggressive prostate cancer and 478 age- and ethnicity-matched controls. Diet was assessed with a semiquantitative food frequency questionnaire, and nine COX-2 tag single nucleotide polymorphisms (SNPs) were genotyped. We used logistic regression models to estimate odds ratios (ORs) for association and interaction. RESULTS: Increasing intake of LC n-3 was strongly associated with a decreased risk of aggressive prostate cancer (trend p<=0.0001). The OR (95% CI) for prostate cancer comparing the highest to the lowest quartile of omega-3 intake was of 0.37 (0.25 – 0.54). The LC n-3 association was modified by SNP rs4648310 (+8897 A/G), flanking the 3′ region of COX-2 (interaction p=0.02). In particular, the inverse association was even stronger among men with this variant SNP. This reflected the observation that men with low LC n-3 intake and the variant rs4648310 SNP had an increased risk of disease (OR = 5.49; 95% CI: 1.80-16.7), which was reversed by increasing intake of LC n-3. CONCLUSIONS: Dietary LC n-3 PUFAs appear protective for aggressive prostate cancer, and this effect is modified by the COX-2 SNP rs4648310. Our findings support the hypothesis that LC n-3 may impact prostate inflammation and carcinogenesis through the COX-2 enzymatic pathway.